2002
DOI: 10.1203/00006450-200209000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Spatial Learning and Hyperactivity in Developing Rats Exposed to Intermittent Hypoxia

Abstract: Obstructive sleep apnea (OSA) is a frequent medical condition and is associated with cognitive impairments in adults and with hyperactivity and decreased school performance in children. In an adult rodent model, intermittent hypoxia (IH), such as occurs in OSA, is associated with neurodegenerative changes in the hippocampus and cortex and with spatial learning deficits. Because a unique developmental window of neural vulnerability to IH is present, we hypothesized that exposure to IH throughout the vulnerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(113 citation statements)
references
References 23 publications
8
102
2
1
Order By: Relevance
“…Neurological deficits have also been associated with chronic intermittent hypoxia such as that encountered in OSA. Row et al reported an association between intermittent hypoxia, elevated lipid peroxidation, and oxidative stress in rat brain tissue [93]. This same study also demonstrated that impairments in spatial learning induced by redox alterations were attenuated by antioxidant treatment.…”
Section: Obstructive Sleep Apnea and Oxidative Stressmentioning
confidence: 55%
“…Neurological deficits have also been associated with chronic intermittent hypoxia such as that encountered in OSA. Row et al reported an association between intermittent hypoxia, elevated lipid peroxidation, and oxidative stress in rat brain tissue [93]. This same study also demonstrated that impairments in spatial learning induced by redox alterations were attenuated by antioxidant treatment.…”
Section: Obstructive Sleep Apnea and Oxidative Stressmentioning
confidence: 55%
“…In one community survey, boys under age 8 showed an association between parent-reported snoring and hyperactivity, but older children and girls under 8 showed no such association [76]. Although this finding requires replication, it parallels analogous behavioral changes observed in male rat pups, but not female pups, after exposure to intermittent hypoxia [77].…”
Section: Risk and Resilience Factorsmentioning
confidence: 85%
“…However, this study aimed to elaborate on up to what extent IH further improves the positive effects of physical training on cognitive performance and QoL. On the one hand, severe levels of IH are associated with neurocognitive morbidity [42,43]. On the other hand, mild hypoxic training is not only innocuous [44], but mild hypoxic preconditioning also has a protective effect on neural viability of vulnerable hippocampal cells [45].…”
Section: Discussionmentioning
confidence: 99%